2023
DOI: 10.1073/pnas.2212121120
|View full text |Cite|
|
Sign up to set email alerts
|

The book of Lambda does not tell us that naturally occurring lysogens of Escherichia coli are likely to be resistant as well as immune

Abstract: The most significant difference between bacteriophages functionally and ecologically is whether they are purely lytic (virulent) or temperate. Virulent phages can only be transmitted horizontally by infection, most commonly with the death of their hosts. Temperate phages can also be transmitted horizontally, but upon infection of susceptible bacteria, their genomes can be incorporated into that of their host’s as a prophage and be transmitted vertically in the course of cell division by their lysogenic hosts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…used model-based and in vitro experiments to show that temperate λ phage leads to similarly high levels of lysogenic and phage-resistant non-lysogenic E. coli after one day, whereas the presence of virulent λ phage results in a numerical dominance of the latter. 46 Not only are our results consistent with these observations, but we also show that even an increased frequency of lysis by temperate phages can lead to elevated phage resistance, reaching levels similar to those seen with a strictly lytic phage. For a greater understanding of this relationship between lysis/lysogeny by temperate phages and phage resistance in the host bacterium, more detailed genetic studies will be needed.…”
Section: Discussionsupporting
confidence: 89%
“…used model-based and in vitro experiments to show that temperate λ phage leads to similarly high levels of lysogenic and phage-resistant non-lysogenic E. coli after one day, whereas the presence of virulent λ phage results in a numerical dominance of the latter. 46 Not only are our results consistent with these observations, but we also show that even an increased frequency of lysis by temperate phages can lead to elevated phage resistance, reaching levels similar to those seen with a strictly lytic phage. For a greater understanding of this relationship between lysis/lysogeny by temperate phages and phage resistance in the host bacterium, more detailed genetic studies will be needed.…”
Section: Discussionsupporting
confidence: 89%
“…A noteworthy aspect of our results is the persistence of the PF4 strain in co-culture with the lysogenic strain P1.1 in the presence of the Valp1 phage. This phenomenon has been explored by other authors in E. coli and the lambda phage, where it was observed that under similar conditions, a predominance of lysogenic bacteria and non-lysogenic strains resistant to the phage also occurred [ 40 ]. However, in that case, both bacterial population maintained a similar proportion.…”
Section: Discussionmentioning
confidence: 99%
“…To my knowledge, the OPS protective efficiency has never been assessed on E. coli grown anaerobically and/or on starved cells that would better mimic the conditions in the human gut than actively growing aerobic cultures. Interestingly, the environmental E. coli isolates that were lysogenic by phages closely related to the phage lambda or by P2-like phages were not only immune to the phages encoded by their own prophages but also resistant to (unable to adsorb) these viruses [65]. The authors explain this finding by expected evolution of the resistance in lysogens that initially were only immune to phages.…”
Section: Ops Restricts Prophage Acquisitionmentioning
confidence: 99%
“…I, however, speculate that the tested strains could be completely protected by the O antigen or rendered almost non-penetrable for lambda-like or P2-like phages. Unfortunately, the mechanism of the resistance observed [65] was not analyzed in the study.…”
Section: Ops Restricts Prophage Acquisitionmentioning
confidence: 99%